Investigating the effect of the aging process on LDPE composites with UV protective additives - SANCAK, ERHAN (SAGE PUBLICATIONS LTD, 2022)
The contact with ultraviolet rays coming from sunlight causes color changes and deterioration in the main chain structures of composites in outdoor applications and affects the physical and mechanical properties of composite materials negatively. Photodegradation can be slowed and the mechanical strength of composite structures can be improved with adding photostabilizers in polymer matrix production. In this study, we modified low-density polyethylene (LDPE) polymer with an amine light stabilizer (Chimassorb 944), a light absorbent (Tinuvin 326), and an antioxidant (Irganox 1010) and then reinforced with jute fabric (JF). We examined the effect of protective additives, which are used to reduce the harmful effects of sunlight, on JF-reinforced LDPE composites. The color change, physical, and mechanical properties of the composites were determined after 120- and 240-h accelerated aging processes. The results indicate that both the antioxidants and the amine light stabilizers were more effective photostabilizers for JF-reinforced LDPE composites than the absorbents.
Keywords: Low-density polyethylene; jute fiber reinforced; UV protective; thermoplastic composite; aging process; DENSITY POLYETHYLENE COMPOSITES; MECHANICAL-PROPERTIES; NATURAL FIBER; POLYMER COMPOSITES; UNSATURATED POLYESTER; SURFACE MODIFICATION; COUPLING AGENT; ULTRAVIOLET; PERFORMANCE; PHOTODEGRADATION